2017
DOI: 10.18203/2320-1770.ijrcog20173459
|View full text |Cite
|
Sign up to set email alerts
|

Clinico pathological study of ovarian neoplasms

Abstract: Background: Ovarian tumors are common form of neoplasm in women and account for 30% of female genital tract cancers. Ovarian cancer is the sixth most common cancer in women and the leading cause of death in women with gynaecological malignancy. Due to inefficient diagnosis/prognosis strategies mainly due to the lack of specific symptoms at the initial stage of the disease about 70% cases diagnose at advanced stage when the metastatic tumor has acquired drug resistant phenotype.Methods: Prospective study of two… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
5
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(6 citation statements)
references
References 2 publications
1
5
0
Order By: Relevance
“…Baru et al report distension in 43.18% benign and 70.49% women with malignant tumors. 13 We found that women with cancers had a higher probability of having distension in abdomen as compared to those with benign lesions (OR=5, 95% CI 1.03-24.17, p=0.01) comparable to Goff et al (odds ratio=7.4, 95% confidence interval [CI], 3.8-14.2) ( Table 3). 16 The size of the tumor did not correlate with presence of cancer in this study (likelihood ratio χ2=7.55, p=0.255) ( Table 4).…”
Section: Discussionsupporting
confidence: 59%
See 2 more Smart Citations
“…Baru et al report distension in 43.18% benign and 70.49% women with malignant tumors. 13 We found that women with cancers had a higher probability of having distension in abdomen as compared to those with benign lesions (OR=5, 95% CI 1.03-24.17, p=0.01) comparable to Goff et al (odds ratio=7.4, 95% confidence interval [CI], 3.8-14.2) ( Table 3). 16 The size of the tumor did not correlate with presence of cancer in this study (likelihood ratio χ2=7.55, p=0.255) ( Table 4).…”
Section: Discussionsupporting
confidence: 59%
“…Presence of lump in abdomen as a complaint has been reported from 43% to 78% in various studies. 12,13,15,16 We found that the odds of reporting a mass in abdomen were significantly greater in women with cancers compared to those with benign tumors (OR= 4.9, 95% CI 1.07-24.06, p=0.01). Ebell et al in a systematic review reported the likelihood ratio of 30 for presence of an abdominal mass and 16 for distension of abdomen.…”
Section: Discussionmentioning
confidence: 75%
See 1 more Smart Citation
“…22 Pain in the abdominal region was reported by 77.05% of patients, swelling by 70.49%, the presence of ascites by 57.38%, the presence of a mass in the abdominal region by 44.90%, and other constitutional symptoms such as "gastrointestinal distress, weakness, menstrual disorders, and urinary symptoms" by 29.5%, 16.4%, 3.28%, and 3.282%, respectively in Baru et al's study. 23 At a cut off of 35, 37.50% had <35 U/ml CA-I25 and 62.50% had >35 U/ml CA-I25. Among the patients analysed by Kamath et al, 62% had CA-125 levels over 100 U/l, 16% had levels between 35 and 100 U/l, and 22% had levels below 35 U/l.…”
Section: Discussionmentioning
confidence: 94%
“…21 Similar distribution was seen in In the research by Baru et al, only 22.22 percent of patients with ovarian tumours were nulliparous, while the remaining 77.78 percent were multiparous. 23 With regards to clinical presentation, 57.50% presented with pain abdomen, 40% with menstrual irregularities, 75% with mass per abdomen, 32.5% with abdominal distension, 27.5% with white discharge and 32.5% with bladder disturbances. Laul et al reported 44.3% had pain abdomen, 35.1 mass per abdomen, 8.2% with menstrual complaints, 12.4% with infertility, 25.8% had pressure symptoms in their study.…”
Section: Discussionmentioning
confidence: 99%